2009
DOI: 10.1001/archoto.2008.505
|View full text |Cite
|
Sign up to set email alerts
|

Expression Profiling of Inflammatory Mediators in Pediatric Sinus Mucosa

Abstract: Objective To evaluate gene expression by microarray analyses of inflammatory mediators in the sinus mucosa of children with or without chronic rhinosinusitis (CRS). Design Prospective molecular genetics analysis of sinus mucosa from pediatric CRS and control patients. Subjects Eleven CRS patients who underwent endoscopic sinus surgery and ten children who underwent craniofacial resection or neurosurgical procedures. Interventions Gene expression levels of sinus tissue from 6 CRS and 6 control patients we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 24 publications
0
20
0
Order By: Relevance
“…S100A9 is overexpressed in nasal secretory cells from CRS patients with nasal polyps (28), as well as nasal mucus (29) and nasal lavage fluid from CRS patients (19). S100A8 is overexpressed in sinonasal mucosa tissue from patients with CRS with nasal polyps (30,31).…”
Section: Discussionmentioning
confidence: 99%
“…S100A9 is overexpressed in nasal secretory cells from CRS patients with nasal polyps (28), as well as nasal mucus (29) and nasal lavage fluid from CRS patients (19). S100A8 is overexpressed in sinonasal mucosa tissue from patients with CRS with nasal polyps (30,31).…”
Section: Discussionmentioning
confidence: 99%
“…To gain insights into SMG hyperplasia in the upper respiratory tract, gene expression microarray analyses were performed to identify differences in global and specific gene expressions in the sinus mucosa of control and CRS patients. Our initial study identified and validated specific inflammatory and innate immune mediator genes that are upregulated in CRS and control sinus mucosa (18). Here, we identify glandular gene products differentially expressed in the sinus mucosa of control, CRS, and CRS/CF patients, and we evaluate their cellular localization in SMGs.…”
Section: Clinical Relevancementioning
confidence: 96%
“…Sinus tissue was obtained from patients with CRS who underwent functional endoscopic sinus surgery at Children's National Medical Center (CNMC, Washington, DC) for CRS refractory to medical management. Exclusion criteria for the control population and the criteria for diagnosing CRS were described previously (18). A diagnosis of CRS in the CRS/CF cohort was based on a combination of clinical presentation, endoscopic nasal examinations, and computerized tomography imaging of the paranasal sinuses.…”
Section: Specimens Of Sinus Mucosamentioning
confidence: 99%
See 2 more Smart Citations